The Qurʾān and the Future of Islamic Analytic Theology - Abdelnour, Mohammed Gamal (Religions, 2023)
Islamic analytic theology emerges into an uncharted territory that is dominated by two loosely defined areas: analytic philosophy and analytic theology. As a nascent field, this article argues that for Islamic analytic theology to move forward, it needs to place the Qurʾān at its centre. To have a clear understanding of our terms, I begin by attempting a definition of Islamic analytic theology. Taking a normative approach to the subject, I consolidate the discussion with five methodical questions. Firstly, what has been going on in Islamic theology? (The descriptive task). Secondly, why has this been going on? (The interpretative task). Thirdly, what ought to be going on? (The normative task). Fourthly, how might we, as Muslim theologians, respond? (The pragmatic task). Fifthly, why should Muslim theologians conduct analytic theology? (The functional task) To situate Islamic analytic theology within this wider discussion, I end the article by offering some insights on how Islamic analytic theology relates to old Kalām. By the end of the article, we will have laid the groundwork showing the way forward for a more developed Islamic analytic theology.